Pengaruh Kompetensi Dan Disiplin Terhdap Kinerja Pegawai Dengan Komitmen Organisasional Sebagai Variabel Intervening Pada Dinas Pendidikan Dan Kebudayaan Kab.Agam - Atifah Sakinah; Ramdani Bayu Putra; Nila Pratiwi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
.This research aims to find out and analyze the influence of Competency and Discipline on Employee Performance through Organizational Commitment. For District Education and Culture Service Office Employees. Agam. The sample used was a saturated sample, where the entire population was sampled, namely 75 respondents. The data collection technique is through a questionnaire that has been tested for validity and reliability. Partial Least Square (PLS) was used to test the hypothesis in this research using SmartPLS 4.0. The results of this research show that there is a positive and significant influence of Competency on Organizational Commitment. There is a positive and significant influence of discipline on organizational commitment. There is a significant positive Competence on Employee Performance. There is a positive and significant Discipline on Employee Performance. There is a positive and insignificant influence of Organizational Commitment on employee performance. There is a positive and insignificant influence of Competency on Employee Performance through Organizational Commitment and there is a positive and insignificant influence of Discipline on Employee Performance through Organizational Commitment